Grapevine stilbene synthase cDNA only slightly differing from chalcone synthase cDNA is expressed in Escherichia coli into a catalytically active enzyme - Melchior, Frauke; Kindl, Helmut (FEBS letters, 1990)
Stilbene synthase is responsible for the formation of resveratrol and other stilbenes which function in grapevine as phytoalexins. A full-length stilbene synthase cDNA was prepared from grapevine mRNA and sequenced. The insert in pSV25 coding for a polypeptide with 392 amino acids was inserted into the vectors pKK233-2 and pDS12/RBSII-2, respectively. Expression of the cDNA in Escherichia coli yielded an enzyniatically active dimer exhibiting solely stilbene synthase activity. The protein was characterized by enzyme activity and Western blot analysis.
Gesehen am 07.09.2023